Conservation agriculture impacts on soil carbon sequestration under a cotton (Gossypium hirsutum)-wheat (Triticum aestivum) system in the Indo-Gangetic plains - JOSEPH, ANN MARIA; BHATTACHARYYA, RANJAN; DAS, T K; SHARMA, D K; ROY, PLABANI; JAT, S L (The Indian Journal of Agricultural Sciences, 2023)
Despite many studies reporting conservation agriculture (CA) impacts on soil organic carbon (SOC) sequestration, the impacts of long-term permanent bed planting under CA on SOC sequestration are rarely reported. Hence, this study assessed the permanent bed planted CA impacts on SOC sequestration rates in 0–30 and 30–60 cm soil depths under a cotton (Gossypium hirsutum L.)-wheat (Triticum aestivum L.) system in the Indo-Gangetic Plains (IGP). The treatments comprised diverse combinations of tillage and residue retention (R), viz. conventional tillage (CT), narrow bed, narrow bed + R, broad bed, broad bed + R, flat bed + R and flat bed. Results indicated that the total SOC stock was ~32, 31 and 29% higher in CA plots than in CT plots (farmers' practice), in 0–30 cm soil depth. The SOC sequestration rate (over CT plots) in the CA plots was ~0.76 Mg C/ha/yr. The broad bed + R, narrow bed + R and flat bed + R plots had appreciably high total SOC sequestration (~0.24 Mg C/ha/yr) compared to CT plots in deep soil layer (30–60 cm). The yield data (2-year mean basis) was recorded highest in the broad bed + R (3.48 tonnes/ha and 8.11 tonnes/ha for cotton and wheat, respectively) and flat bed + R (3.38 tonnes/ha and 8.46 tonnes/ha for cotton and wheat, respectively) treatments showing a positive impact of the adoption of long-term CA in the IGP. Thus, adopting raised beds with residue retention has great potential for higher carbon sequestration and improving yields and can be recommended for sustainable intensification of arable lands in the region.